2019
DOI: 10.1002/jcp.28418
|View full text |Cite
|
Sign up to set email alerts
|

Crocin inhibits the migration, invasion, and epithelial‐mesenchymal transition of gastric cancer cells via miR‐320/KLF5/HIF‐1α signaling

Abstract: The biological activities of crocin, one of the main bioactive compounds of saffron, include anti‐inflammatory, antioxidant, antidepressant, and anticancer effects. Crocin has been shown to trigger the apoptosis of gastric cancer cells, but its effect on the metastasis of gastric cancer cells remains unclear. Krüppel‐like factor 5 (KLF5) and hypoxia‐inducible factor‐1α (HIF‐1α) are important transcription factors in the development of gastric cancer. KLF5 and HIF‐1α expression were analyzed in gastric cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 37 publications
2
52
0
Order By: Relevance
“…In previous studies, the effect of saffron extracts has been poorly investigated in cancer and there is no study on osteosarcoma. Consistent with our observations, crocin, an active constituent of saffron, was shown to impair migration and invasion capacities as well as epithelial–mesenchymal transition (EMT) of HGC‐27 gastric cancer cells . Likewise, crocetin, another bio‐active compound found in saffron, was also reported to inhibit migratory capacities of retinal pigment epithelial cells .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In previous studies, the effect of saffron extracts has been poorly investigated in cancer and there is no study on osteosarcoma. Consistent with our observations, crocin, an active constituent of saffron, was shown to impair migration and invasion capacities as well as epithelial–mesenchymal transition (EMT) of HGC‐27 gastric cancer cells . Likewise, crocetin, another bio‐active compound found in saffron, was also reported to inhibit migratory capacities of retinal pigment epithelial cells .…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with our observations, crocin, an active constituent of saffron, was shown to impair migration and invasion capacities as well as epithelial-mesenchymal transition (EMT) of HGC-27 gastric cancer cells. [18] Likewise, crocetin, another bio-active compound found in saffron, was also reported to inhibit migratory capacities of retinal pigment epithelial cells. [19] In contrast, anther extract of saffron has no effect on migration capacity of HCT 116 colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Crocin is a key bioactive compound with well known anti-inflammatory, anti-oxidant, and anti-cancer effects. In GC, crocin has been found to suppress the migration, invasion, and epithelial-to-mesenchymal transition (EMT) of GC cells by modulating miR-320/KLF5/HIF-1α signaling [28]. Analysis of clinical GC samples revealed that both KLF5 and HIF-1α expression are upregulated in GC tissues and that KLF5 expression is positively correlated with HIF-1α expression.…”
Section: Ncrnas Regulate Hif Expression In Gcmentioning
confidence: 99%
“…Promotes apoptosis and reduces cell invasion by regulating HIF-1α HIF-1α [23] miR-186 Directly regulates HIF-1α and inhibits cell proliferation HIF-1α [24] miR-143 Directly regulates HIF-1α HIF-1α, ZEB2-AS1 [25] PVT1 Enhances multidrug resistance and is associated with lymph node metastasis HIF-1α, MDR1, MRP, mTOR [26,27] miR-320 Upregulated by crocin and regulates HIF-1α by inhibiting KLF5 KLF5 [28] miR-210…”
Section: Mir-18amentioning
confidence: 99%
“…A range of miRNAs has been reported as tumor suppressors or oncogenes for the irreplaceable mechanism in tumor initiation and progression, and as therapeutic targets (10,11). Increasing evidence supports the idea that aberrant miRNA expression serves important roles in tumor hypoxia and is associated with HIF-1α (12,13). HIF-1α is involved in multidrug resistance by regulating miR-27 in gastric cancer cells (14).…”
Section: Introductionmentioning
confidence: 96%